Duration of anuria predicts recovery of renal function after acute kidney injury requiring continuous renal replacement therapy - Jung, Hee-Yeon (Korean J Intern Med, 2016)
BACKGROUND/AIMS: Little is known regarding the incidence rate of and factors associated with developing chronic kidney disease after continuous renal replacement therapy (CRRT) in acute kidney injury (AKI) patients. We investigated renal outcomes and the factors associated with incomplete renal recovery in AKI patients who received CRRT. METHODS: Between January 2011 and November 2013, 408 patients received CRRT in our intensive care unit. Of them, patients who had normal renal function before AKI and were discharged without maintenance renal replacement therapy (RRT) were included in this study. We examined the incidence of incomplete renal recovery with an estimated glomerular filtration rate < 60 mL/min/1.73 m(2) and factors that increased the risk of incomplete renal recovery after AKI. RESULTS: In total, 56 AKI patients were discharged without further RRT and were followed for a mean of 8 months. Incomplete recovery of renal function was observed in 20 of the patients (35.7%). Multivariate analysis revealed old age and long duration of anuria as independent risk factors for incomplete renal recovery (odds ratio [OR], 1.231; 95% confidence interval [CI], 1.041 to 1.457; p = 0.015 and OR, 1.064; 95% CI, 1.001 to 1.131; p = 0.047, respectively). In a receiver operating characteristic curve analysis, a cut-off anuria duration of 24 hours could predict incomplete renal recovery after AKI with a sensitivity of 85.0% and a specificity of 66.7%. CONCLUSIONS: The renal outcome of severe AKI requiring CRRT was poor even in patients without further RRT. Long-term monitoring of renal function is needed, especially in severe AKI patients who are old and have a long duration of anuria.